Designing Distro T-shirts as an Effort to Develop the Creative Entrepreneurship Potential of Teenagers - Candika Nur Rohiman Hamjah; Arif Nur Najmi; Muhamad Rafi Maulana; Reza Fahrian; Linna Ismawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
This study examines the increasing significance of creative entrepreneurship among adolescents by concentrating on distro T-shirt design as a strategic mechanism for its advancement. Distro T-shirts were selected due to their substantial market attractiveness and potential as a vehicle for creative expression with considerable economic significance within the youth demographic. The research was carried out at Second Eight, a community dedicated to nurturing young talent in graphic design and local fashion entrepreneurship. A qualitative methodological approach was adopted, drawing on data from observations of contemporary design trends, comprehensive interviews with distro business proprietors, and an extensive literature review regarding creative entrepreneurship. The results indicate that T-shirt designs that incorporate elements of local identity, social issues, and youth culture can effectively foster engagement and interest in the creative business realm among adolescents. This process not only refines graphic design abilities but also develops skills in digital marketing and independent business management. The study’s SWOT, IFAS, and EFAS analyses further reveal that, despite obstacles such as constrained financial resources and managerial expertise, the brand retains substantial internal strengths and external opportunities for prosperity. In conclusion, the design of distro T-shirts functions as an effective pedagogical instrument for character formation, innovation, and economic empowerment, ultimately nurturing a new generation of creative, autonomous, and sustainable entrepreneurs. This research illustrates a feasible model for leveraging youth creativity to stimulate local innovation and enhance the growth of the creative economy in Indonesia.